2018
DOI: 10.3382/ps/pex310
|View full text |Cite
|
Sign up to set email alerts
|

In ovo injection of ascorbic acid modulates antioxidant defense system and immune gene expression in newly hatched local Chinese yellow broiler chicks

Abstract: The present study was conducted to investigate the effects of in ovo injection of ascorbic acid on antioxidant capacity and immune-related gene expression in the newly hatched local Chinese yellow broiler chicks. Fertile Chinese yellow broiler eggs (n = 90) were assigned to three equal groups. The first group was a non-injected control group. The second group was another control group where the eggs were injected with saline in the air sac after 18 days of incubation. The third group was injected with 3 mg/egg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 25 publications
1
19
0
Order By: Relevance
“…In this study, IOI of naringin in 30 mg increased the weight of recently hatched chickens by stimulating the development of the chick embryo. This is in agreement with other studies in terms of IOI of prebiotic and synbiotic (Miśta et al, 2016), carbohydrates (Ferket & Uni, 2001), and amino acids or antioxidant (El-Senousey et al, 2017).…”
Section: Hatched Chickssupporting
confidence: 93%
“…In this study, IOI of naringin in 30 mg increased the weight of recently hatched chickens by stimulating the development of the chick embryo. This is in agreement with other studies in terms of IOI of prebiotic and synbiotic (Miśta et al, 2016), carbohydrates (Ferket & Uni, 2001), and amino acids or antioxidant (El-Senousey et al, 2017).…”
Section: Hatched Chickssupporting
confidence: 93%
“…To the best of our knowledge, there have been few studies on the effect of IOF of vitamin C on plasma antioxidant capacity of broilers. The only available research results showed that IOF of vitamin C increased GSH-Px and T-AOC activities and decreased malondialdehyde content in plasma of chicks on D1 (27) . However, plasma antioxidant capacity was merely tested on D21 and 42 in this study, and only T-AOC was elevated on D42 in the VC group.…”
Section: Discussionmentioning
confidence: 97%
“…Transcriptomics is based on gene expression profiles, using GO and KEGG databases to perform functional annotation and enrichment analysis. It has been well established that IOF of vitamin C could improve production traits, muscle development and immune function in poultry (14,24) , but the potential regulatory mechanisms were uncleared. Based on the functional analysis of GO and KEGG of differentially expressed genes induced by IOF of vitamin C, our data found that the metabolic pathways and biological processes were extensively regulated during the embryonic period of the spleen growth, such as phosphorus metabolism, nucleotide metabolism and biosynthesis, purine nucleotide metabolism, purine-containing compound metabolism and reproduction of multicellular organisms, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin C can be synthesized endogenously in poultry, but the synthesis ability of chicks is weak, and it is easy to cause vitamin C deficiency under stress stimulation (13) . Previous studies have shown that the immune activity and Accepted manuscript anti-stress ability of broilers can be effectively improved in response to IOF of vitamin C (14,15) . Also, our laboratory had reported that vitamin C supplementation in embryonic period was able to improve plasma antibody levels and regulated immune-related gene expression, thus improved the immune status of broilers (6,16) .…”
Section: Introductionmentioning
confidence: 99%